Improving the security and encryption performance of cloud storage by using elliptic curve cryptography - Ismaeel, Nooruldeen Qutaiba (2016)
Cloud services have emerged as one of the most promising solutions for many real world issues. They can be used in a wide variety of applications ranging from cloud storage, cloud computing, and cloud applications. However, they are a double-edged sword from security and privacy standpoints, especially when storing sensitive data in cloud storage. Therefore, besides secure they require efficient security solutions to obtain the necessary security level. The current security solutions are designed to work mainly on either the client side or the server side, and this strategy may cause a reduction of either the performance of the system or the security of the data. In this thesis, we have proposed a security solution based on an ECC algorithm to improve the security and the performance of the data by dividing the file content and encrypting it on both the server and the client side. The proposed solution improves the performance of the standard ECC and outperforms the AES algorithm in terms of encryption speed and response time.